Doomscrolling and Sleep Quality of School-Age Children in Malang, Indonesia: Doomscrolling and Sleep Quality of School-Age Children in Malang, Indonesia - Oktavianus Dara Dendo; Feriana Ira Handian; Neni Maemunah (LPPM STIKES Guna Bangsa Yogyakarta, 2026)
Background: Excessive doomscrolling may adversely affect children's sleep quality. Furthermore, its affect negative cognitive, emotional, and behavioral consequences include reduced attention, poor academic performance, increased daytime sleepiness, and a higher risk of mood and anxiety disorders. Objective: This study seeks to ascertain the correlation between the duration of doomscrolling and the quality of sleep in school-aged children. Methods: This research employed a quantitative approach with a cross-sectional design. A sample of 87 students was obtained by a simple random sampling method at SDIT Permata Malang, located in the Lowokwaru District of Malang City. The tools employed were the doomscrolling scale questionnaire and the Pittsburgh Sleep Quality Index (PSQI). The analysis employed the Spearman's rho test. Results: The findings indicated an association between doomscrolling and sleep quality in school-age children (p-value = 0.028 (<0.05)) with a correlation coefficient (r) of 0.236. A majority of sixth-grade students at SDIT Insan Permata Malang exhibited low doomscrolling length (52.9%) and good sleep quality (64.4%). Conclusions: Longer doomscrolling behaviour tends to be associated with poorer sleep quality. Subsequent research may evaluate doomscrolling behavior, sleep efficiency, and parental monitoring, utilizing longitudinal and experimental studies.